Pelatihan Pembudidayaan Maggot Sebagai Upaya Peningkatan Potensi Pemanfaatan Sampah Organik dan Menghasilkan Nilai Jual Bagi Masyarakat Desa Sukarame, Kecamatan Balik Bukit, Lampung Barat - Firja, Meyronita; Wansyah, Rio; Khotimah, Chusnul; Sobirin, Yobi; Putri, Reri Eriyana; Soraya, Zhafira Azis; Stiawan, Beni; Khalisa, Nur Ulya; Safitri, Rizki Ariana (Civiliza Publishing, 2024)
One of the villages in Balik Bukit District, West Lampung Regency, Lampung Province is Sukarame Village. The majority of the population in this village are vegetable farmers who only sell their crops to the nearest market, indicating that this village has potential. In addition, although animal protein consumption plays an important role in improving public health, animal protein consumption in Lampung Province is still low. The purpose of this community service is to process agricultural waste through maggot production, while providing a new approach in the form of organic waste processing. Students practice direct cultivation methods after the material delivery session is complete. The results of the study showed that students realized the benefits, understood how to raise maggots as a way to manage organic waste, and had the potential to increase the selling value of the community. In addition, this training can provide opportunities for students to produce maggots independently.